The Effect of Firm Size and Leverage on Profit Management With Ownership Structure as a Moderating - Gilbert Rely (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
This study aims to examine and analyze the effect of firm size and leverage on earnings management with ownership structure as moderating. The sample used is 54 manufacturing firms listed on the Indonesia Stock Exchange for 2015-2017 period, using multiple regression analysis and to measure hypotheses is SPSS 24. The study results are (1) firm size has a positive and not significant effect on earnings management. (2) Leverage has a positive effect on earnings management. (3) Managerial ownership has a negative effect on earnings management. (4) Institutional ownership has a negative and insignificant effect on earnings management. (5) Managerial ownership strengthens the influence of firm size on earnings management. (6) Institutional ownership does not strengthen the influence of firm size on earnings management. (7) Managerial ownership weakens the influence of leverage on earnings management. (8) Institutional ownership weakens the influence of leverage on earnings management.